ナンタイヨウ インドヨウ ク オヨビ リュツォ・ホルムワン オキ ノ カイヒョウ ショウチョウ ノ トクチョウ - 牛尾, 収輝; ウシオ, シュウキ; Ushio, Shuki (2006)
P(論文) 1970年代以降の衛星データを用いて,南大洋インド洋区及びその中のリュツォ・ホルム湾沖における海氷消長の特徴を調べた.インド洋区で海氷域面積が最大値に達する時期は10月で,他の海域と比べて1カ月遅い.この遅れの一因として,インド洋区の西に位置するウェッデル海区から沖合流氷が東に輸送されることが寄与していると考えられる.海氷融解期の11-12月の面積減少率はインド洋区で最も大きいことも示された.リュツォ・ホルム湾沖の海氷消長については,東経40度線上の海氷縁位置の変化に着目した.その結果,秋～初冬の海氷域拡大期には氷縁の北上開始が他の海域よりも1-2カ月遅れること,春の海氷域縮小期には急速に氷縁が後退する傾向が顕著であることがわかった.この東経40度付近の海氷消長はインド洋区の中でも顕著な特徴であり,同海域におけるコスモノートポリニアの形成との関連が示唆される. Characteristics of sea ice variations in the Indian Ocean sector and off Lutzow-Holmbukta, Antarctica, have been described with satellite data archived since the 1970s. In the Indian Ocean sector, the period of maximum ice extent is generally reached in October, a month later than in other sectors. The probable reason for the delay is eastward sea-ice drift from the Weddell Sea sector west of the Indian Ocean sector. During the ice melt season, the highest rate of ice retreat from November to December appears in the Indian Ocean sector. Also, the ice edge along 40 degrees east longitude off Lutzow-Holmbukta shows a remarkable delay pattern at the beginning of autumn ice extent season and rapid retreat of the ice edge in the spring melt season. These features are qualitatively explainable due to Cosmonaut Polynya formation. departmental bulletin paper